PENGARUH PEMBERIAN PAKAN KOMPLIT BERBASIS JERAMI PADI DAN AMPAS KELAPA TERHADAP KONSUMSI BAHAN KERING, BAHAN ORGANIK DAN PROTEIN KASAR PADA KELINCI PERTUMBUHAN - Tola, Ardianus Yanuarius; Marhaeniyanto, Eko; Iskandar, Ahmad (Universitas Tribhuwana Tunggadewi, 2019)
The study determine the effect of providing rice straw and coconut pulp complete feed with crude protein (CP) 15% on dry matter intake (DMI), organic matter intake (OMI) and crude protein intake (CPI) in New Zealand White rabbits. The research material consisted of 20 rabbits with an initial body weight of 1081.05 ± 13.71gram/head. The constituent feed ingredients are composed of yellow corn, rice bran, soybean meal, fish meal molasses, minerals & salt. The study used a randomized block design trial (RBD) consisting of 4 treatments 5 replications, namely P0 = yellow corn, bran, soybean meal, fish meal molasses, minerals & salt (concentrate constituent material) without rice straw and coconut pulp; P1 = Coconut pulp 10% + concentrate constituent material; P2 = 5% coconut pulp and 5% rice straw + concentrate constituent material; P3 = Rice straw 10% + concentrate constituent material. The results showed a very significant effect (P